Efficient Carbon-Based CsPbBr3 Inorganic Perovskite Solar Cells by Using Cu-Phthalocyanine as Hole Transport Material - Liu, Zhiyong; Sun, Bo; Liu, Xingyue; Han, Jinghui; Ye, Haibo; Shi, Tielin; Tang, Zirong; Liao, Guanglan (Nano-Micro Letters, 2018)
Metal halide perovskite solar cells (PSCs) have attracted extensive research interest for next-generation solution-processed photovoltaic devices because of their high solar-to-electric power conversion efficiency (PCE) and low fabrication cost. Although the world’s best PSC successfully achieves a considerable PCE of over 20% within a very limited timeframe after intensive efforts, the stability, high cost, and up-scaling of PSCs still remain issues. Recently, inorganic perovskite material, CsPbBr3, is emerging as a promising photo-sensitizer with excellent durability and thermal stability, but the efficiency is still embarrassing. In this work, we intend to address these issues by exploiting CsPbBr3 as light absorber, accompanied by using Cu-phthalocyanine (CuPc) as hole transport material (HTM) and carbon as counter electrode. The optimal device acquires a decent PCE of 6.21%, over 60% higher than those of the HTM-free devices. The systematic characterization and analysis reveal a more effective charge transfer process and a suppressed charge recombination in PSCs after introducing CuPc as hole transfer layer. More importantly, our devices exhibit an outstanding durability and a promising thermal stability, making it rather meaningful in future fabrication and application of PSCs. Highlights: 1 Cu-phthalocyanine was employed as hole transport material for CsPbBr3 inorganic perovskite solar cells. 2 The optimal device acquires a decent power conversion efficiency of 6.21%, over 60% higher than those of the hole transport material-free devices. 3 The device exhibits an outstanding durability and a promising thermal stability.